2014
DOI: 10.1021/jp411297s
|View full text |Cite
|
Sign up to set email alerts
|

Organic Free Radicals in Clathrate Hydrates Investigated by Muon Spin Spectroscopy

Abstract: Very little is known about the behavior of free H atoms and small organic radicals inside clathrate hydrate structures despite the relevance of such species to combustion of hydrocarbon hydrates. Muonium is an H atom analog, essentially a light isotope of hydrogen, and can be used to probe the chemistry of H atoms and transient free radicals. We demonstrate the first application of muon spin spectroscopy to characterize radicals in clathrate hydrates. Atomic muonium was detected in hydrates of cyclopentane and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…26 In one of them Mu takes a quasi-axial orientation with respect to the ring, and the other quasi-equatorial. The observation of a single radical implies that the two conformers rapidly interconvert, presumably as a result of non-planar ring fluctuations as suggested by ESR studies of similar 5-membered alicyclic radicals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…26 In one of them Mu takes a quasi-axial orientation with respect to the ring, and the other quasi-equatorial. The observation of a single radical implies that the two conformers rapidly interconvert, presumably as a result of non-planar ring fluctuations as suggested by ESR studies of similar 5-membered alicyclic radicals.…”
Section: Resultsmentioning
confidence: 99%
“…This one is part of a spectrum obtained from neat liquid cyclopentene at -10°C, and can be assigned to the α-H of the muoniated cyclopentyl radical. 26 Resonances of the ΔM = 1 type only occur if there is some off-diagonal coupling of states, as can happen with the anisotropic part of the hyperfine interaction. This muon spin flip occurs at the field where ν R1 is zero:…”
Section: -2mentioning
confidence: 99%
“…CHMu group is related to the known muon hfc by the ratio of their magnetic moments (0.301) and additional zero-point vibrational isotope effects. 35 The computational predictions provide further guidance and lead to the assignments shown in Tables 2 and 3. There is good agreement between the experimental and computed hfcs for radicals 3 and 4 (derived from thiophene), and for most of those for 5 and 6 (derived from pyrrole).…”
Section: Identification Of Radical Productsmentioning
confidence: 70%
“…In previous work we have shown that muonium can be unambiguously detected in clathrate hydrates of cyclopentane and tetrahydrofuran, 35 whereas cyclopentene, 2,5-dihydrofuran, 2,3-dihydrofuran, and furan itself all give rise to muoniated radicals. 35,36 It is significant that two distinct radical products were identified for each of furan and 2,3-dihydrofuran, corresponding to Mu addition at inequivalent unsaturated carbon atoms.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation